Mangifera indica 'Namdokmai' Prevents Neuronal Cells from Amyloid Peptide Toxicity and Inhibits BACE-1 Activities in a Drosophila Model of Alzheimer's Amyloidosis. - Temviriyanukul, P.; Kittibunchakul, S.; Trisonthi, P.; Kunkeaw, T.; Inthachat, W.; Siriwan, D.; Suttisansanee, U. (Pharmaceuticals, 2022)
Alzheimer's disease (AD) is a progressive neurological illness with few effective treatments. Thus, ameliorating the effects of AD using natural products has attracted global attention with promising efficacy and safety. In this study, ten tropical fruits including Ananas comosus 'Phulae', Ananas comosus 'Pattavia', Carica papaya 'Khaekdum', Carica papaya 'Khaeknuan', Durio zibethinus 'Monthong', Durio zibethinus 'Chanee', Psidium guajava 'Kimju', Psidium guajava 'Keenok', Mangifera indica 'Kaew' and Mangifera indica 'Namdokmai' were screened for their inhibitory activities against the key enzymes, cholinesterases and ?-secretase (BACE-1), involved in AD pathogenesis. The top three fruit extracts with promising in vitro anti-AD activities were further investigated using rat pheochromocytoma PC-12 neuronal cell line and Drosophila AD model. Data showed that M. indica 'Kaew', M. indica 'Namdokmai' and P. guajava 'Kimju' reduced A?1-42-mediated neurotoxicity by promoting glutathione-dependent enzymes, while M. indica 'Namdokmai' limited A?1-42 peptide formation via BACE-1 inhibition and amended locomotory behavior of the Drosophila AD model. Results indicated the potential anti-AD properties of tropical fruits, particularly M. indica 'Namdokmai' in the prevention of A?1-42-mediated neurotoxicity and as a BACE-1 blocker.